Intelligent flock of surface vehicles for collecting solid waste in bodies of water - Ong, Carl Heinrich I. (Animo Repository, 2023)
As of 2023, the Philippines has been identified as one of the largest contributors to plastic waste in the oceans. The reason for that is the inefficiencies in how the country handles its waste. Focusing mainly on manual labor and voluntarism, the country is only able to segregate a handful of solid waste objects, consequently succumbing to the harmful effects of water pollution.In order to ensure that the amount of plastic waste being collected far outweighs the amount being generated and entering the Philippines’ bodies of water, a new approach has to be made: one where the repetitive task of identifying and collecting plastic waste can be automated. The proponents of this study, utilizing features such as object detection and water drone technology, propose the idea of an intelligent flock of surface vehicles—ones that are unmanned, and are able to identify plastic bottles and subsequently move to their location, all the while communicating with like-minded water drones in the hopes of performing their waste segregation duties in a coordinated manner with respect to the specific regions that they are deployed in. The study includes delving into the precision of the prototype’s ability to identify plastic bottles, its efficiency in coordinating with a group of similar surface vehicles, and how they all tie in together to ensure that the proposed system can be a viable option to combat plastic waste in the Philippine waters.